The Role of Estrogen in Anxiety-Like Behavior and Memory of Middle-Aged Female Rats - Renczés, Emese; Borbélyová, Veronika; Steinhardt, Manuel; Höpfner, Tim; Stehle, Thomas; Ostatníková, Daniela; Celec, Peter (Frontiers in Endocrinology, 2020)
Aging in women is associated with low estrogen, but also with cognitive decline and affective disorders. Whether low estrogen is causally responsible for these behavioral symptoms is not clear. Thus, we aimed to examine the role of estradiol in anxiety-like behavior and memory in rats at middle age. Twelve-month old female rats underwent ovariectomy (OVX) or were treated with 1mg/kg of letrozole – an aromatase inhibitor. In half of the OVX females, 10µg/kg of 17β-estradiol was supplemented daily for four weeks. Vehicle-treated sham-operated and OVX females served as controls. For behavioral assessment open field, elevated plus maze and novel object recognition tests were performed. Interaction between ovarian condition and additional treatment had the main effect on anxiety-like behavior of rats in the open field test. In comparison to control females, OVX females entered less frequently into the center zone of the open field (p<0.01) and showed lower novel object discrimination (p=0.05). However, estradiol-supplemented OVX rats had higher number of center-zone entries (p<0.01), spent more time in the center zone (p<0.05), and showed lower thigmotaxis (p<0.01) when compared to OVX group. None of the hormonal manipulations affected anxiety-like behavior in the elevated plus maze test significantly, but a mild effect of interaction between ovarian condition and treatment was shown (p=0.05). . In conclusion, ovariectomy had slight negative effect on open-field ambulation and short-term recognition memory in middle-aged rats. In addition, a test-specific anxiolytic effect of estradiol supplementation was found. In contrast, letrozole treatment neither affected anxiety-like behavior nor memory.